2021
DOI: 10.1101/2021.07.16.452691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling lung cell development using human pluripotent stem cells

Abstract: Human PSC (hPSC) differentiations can capture developmental phenotypes and processes and are useful for studying fundamental biological mechanisms driving tissue morphogenesis and cell lineage development. Here, we show for the first time the temporal development of lung cell lineages using hPSC that model developmental milestones observed in primary tissue, the generation of renewable fetal lung epithelial organoids, and the functional utility of the lung models at different differentiation stages for Cystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…These markers included mucin 5AC (MUC5AC) for goblet cells, Forkhead box J1 (FOXJ1) for multi-ciliated cells, and mucin 16 (MUC16) and CFTR for surface airway epithelial cells. Ionocytes are rarely observed in these iPSC-derived cultures ( Hawkins et al, 2021 ; Ngan et al, 2021 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These markers included mucin 5AC (MUC5AC) for goblet cells, Forkhead box J1 (FOXJ1) for multi-ciliated cells, and mucin 16 (MUC16) and CFTR for surface airway epithelial cells. Ionocytes are rarely observed in these iPSC-derived cultures ( Hawkins et al, 2021 ; Ngan et al, 2021 ). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue to be deepened is the contribution of niche stromal cells to the growth and differentiation of epithelial cells, which is underrepresented in current protocols [55,97]. Recent data show that robust methods of generating renewable sources of basal stem cells from iPSCs with the capacity to differentiate into multi-epithelial cell types are now available [117,118]. Airway organoids derived from these basal stem cells can be used to generate ALI cultures and provide a unique tool to study CFTR function before and after gene correction [118].…”
Section: Discussionmentioning
confidence: 99%
“…Airway organoids derived from these basal stem cells can be used to generate ALI cultures and provide a unique tool to study CFTR function before and after gene correction [118]. On the other hand, these airway organoids possess some drawbacks, such as long-term swelling and the lack of rare cell types, including neuroendocrine cells and ionocytes [117]. Therefore, further improvement is needed if iPSC-derived airway organoids might be used to model the CF disease in a more detailed manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent sequencing technologies have mapped the faithful lung lineage differentiation of iPSC in modeling development compared to their in vivo tissue counterparts ( Miller et al, 2019 ; Hurley et al, 2020 ; Hawkins et al, 2021 ). It has also been shown that iPSC-derived fetal lung cells transcriptionally match late pseudoglandular fetal lung epithelial cells ( Ngan et al, 2021 ). Human iPSC-derived fetal lung cells provide an opportunity to determine the role of CFTR in pseudoglandular lung epithelial development.…”
Section: Introductionmentioning
confidence: 99%